Physiological factors affecting the mechanical performance of peripheral muscles: A perspective for long COVID patients through a systematic literature review - Suba Rao, Harinivas Rao; Hamzaid, Nur Azah; Ahmad, Mohd Yazed; Hamzah, Norhamizan (Frontiers in Physiology, 2022)
Background: Peripheral muscle weakness can be measured quantitatively in long COVID patients. Mechanomyography (MMG) is an alternative tool to measure muscle strength non-invasively. Objective: This literature review aims to provide evidence on the efficacy of MMG in measuring muscle strength for long COVID patients and to determine the physiological factors that may affect the use of MMG in assessing muscle performance. Methods: A systematic literature review was conducted using EBSCO’s MEDLINE Complete. A total of five out of 2,249 potential publications fulfilled the inclusion criteria. Results: The selected studies addressed muscle performance based on the physiological effects of age, gender, and physical activity level. MMG is sensitive in measuring muscle strength for long COVID patients due to its higher signal-to-noise ratio and lightweight accelerometers. Its neglectable skin impedance and low risk of influences during the recording of surface motions make MMG a reliable tool. Conclusion: Muscle performance is affected by age, gender, and physical activity level. Sensors, such as MMG, as well as the length of the muscle and the characteristics of the muscle activity, are important considerations when choosing a sensor for diagnostic evaluation. The efficacy of MMG in measuring muscle strength for long COVID patients and the physiological factors that may affect the use of MMG in assessing muscle performance are discussed.